PENGARUH RASIO LIKUIDITAS,PROFITABILITAS DAN LEVERAGE TERHADAP RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - manik, nova adeliana; Tipa, Handra (SCIENTIA JOURNAL, 2020)
this study discusses liquidity, profitability and leverage on the returns of manufacturing company shares on the indonesia stock exchange for the period 2015-2019, both partially and simultaneously. in this research population consists of 58 companies included in the sector on the indonesia stock exchange securities,research samples in 27 manufacturing companies in indonesia stock exchange 2015-2019. data collection techniques that are used are data processing with SPSS 21. data analysis methods used are with multiple linear regression method. T test results show that liquidity has a significant positive effect onstock returns, and leverage has a negative effect on stock returns, the results of the F test analysis explain that liquidity,profitability, and leverage simultane ously have a significant effect on stock returns. keyword: stock return; leverage; profitability; liquidity.